Dynamic capabilities trends: A brief review of the state of the art - Patricio, V. S.; Pereira, L. F.; Santos, J. P. (2019 IEEE International Conference on Engineering, Technology and Innovation (ICE/ITMC), 2019)
Dynamic capabilities (DC) is a relatively young area, being a subject of interest and research of the recent year, hence its literature is mainly conceptual. In this article, we review briefly the current state-of- The-art, the literature over the past 10 years and how its related with competitive advantages and management. This article presents a brief literature review, proposing to guide future research, which will be conducted in a near future and work on a dynamic competency model which allows organizations to continuously develop these skills, aligned with the best models and to develop more effective strategies, which will lead to a continuously improvement.